Sustainability orientation of generation Z and its role in their choice of employer: A comparative qualitative inquiry of India and United States - Debashish Sengupta; Manisha Mathews; Lasondrick Bridges; Roshan D'Costa; Bettina Lynda Bastian (Administrative Sciences, 2024)
This article critically analyses and compares the sustainability orientation of Generation Z in India and the United States and examines its role in their employer selection, using the Theory of Planned Behaviour. Our qualitative study employs the Narrative Inquiry method and includes 30 participants-15 from India and 15 from the United States-aged between 19 and 26 years, who are either currently employed or preparing to enter the workforce within the next few years. Data were collected through in-depth interviews. The findings of our research show that subjective norms and contextual realities can play a significant role in shaping Generation Z's personal attitudes towards sustainability and their perceived behavioural control in making important life decisions, such as choosing an employer. These findings contribute significantly to the literature on Generation Z's sustainability orientation and bear important implications for the higher education sector and employers.
Keywords: 350; sustainability; Generation Z; choice of employer